Judaism and Jesus - Garber, Zev 1941-; Hanson, Kenneth 1953- (Newcastle upon Tyne, UK Cambridge Scholars Publishing, 2020)
"Teaching Jewish studies" / Zev Garber -- "Jesus in the trenches / Zev Garber -- "One in Christ" / Zev Garber -- "Jewish Jesus: partisan's imagination" / Zev Garber -- "Jesus, the Pharisees and the sages" / Kenneth Hanson -- "The shema, the historical Jesus and messianic Judaism" / Kenneth Hanson -- "Threading the needle: the Ḥasidim and the Nazarene" / Kenneth Hanson -- "Perpetual dilemma" / Zev Garber -- "Sitting at a common table" / Kenneth Hanson.
This insightful volume represents the "hands-on" experience in the world of academia of two Jewish scholars, one of Orthodox background and the other a convert to the Jewish faith. As a series of separate but interrelated essays, it approaches multiple issues touching both the historical Jesus (himself a pious Jew) and the modern phenomenon of Messianic Judaism. It bridges the gap between the typically isolated disciplines of Jewish and Christian scholarship and forges a fresh level of understanding across religious boundaries. It delves into such issues as the nature and essence of Jesus' message (pietistic, militant or something of a hybrid), and whether Messianic Jews should be welcome in the larger Jewish community. Its ultimate challenge is to view sound scholarship as a means of bringing together disparate faith traditions around a common academic table. Serious research of the "great Nazarene" becomes interfaith discourse. --
Includes bibliographical references and index
Keywords: Jesus Christ -- Jewish interpretations; Messianic Judaism